A systematic narrative review of the involvement of executive functions in flying performance of pilots - Enriquez-Geppert, Stefanie; Smit, Diede; de Boer, Marike C.; Daneshnia, Negin; Lafont, Alex; Dehais, Frédéric (Frontiers in Neuroergonomics, 2024)
Piloting is a complex task that demands robust cognitive functions to handle multiple tasks simultaneously in a constantly changing environment. As a result, cognitive abilities, particularly executive functions (EFs), have gained significant importance in relation to flight performance. However, the specific EFs most critical for predicting flight performance remain unclear. Understanding the exact nature of this relationship has the potential to advance research on pilot selection procedures, cockpit design, and influence cognitive training approaches to ultimately improve flight safety. This systematic review aims to pinpoint the most pertinent EFs for various aspects of airplane piloting. A systematic narrative literature review was conducted with a framework focusing on four EFs: working memory updating, set-shifting, response inhibition, and conflict monitoring, as well as three key aspects of flight performance: flying, navigating, and communicating. The findings suggest that multiple EFs predict flight performance outcomes. Notably, working memory updating significantly predicts the management of communication tasks and the making of critical decisions requiring mental flexibility. However, other specific EFs remain understudied. To advance this research area, we recommend conceptualizing EFs and flying measures based on existing theoretical frameworks, using measures sensitive to specific EFs, evaluating flying performance in simulated or real flights, controlling or accounting for factors that affect EFs and flying performance, and investigating the ameliorative potential of EFs with end results on flight performance.